Sobre las semillas de mango (Mangifera indica) I. Morfologia - Rodriguez, N.N.=700 1 Fuentes, V.; Capote, M.; Alvarez, M.
(Es, En)
Ilus., 20 ref.
Keywords: MANGIFERA INDICA; ANATOMIA DE LA PLANTA; SEMILLAS; CARACTERISTICAS DE LA SEMILLA; PERICARPIO; CUBA; CIENCIA Y TECNICA EN LA AGRICULTURA: CITRICOS Y OTROS FRUTALES